2008
DOI: 10.1007/s00705-008-0113-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the full-length genomic sequences of vesicular stomatitis Cocal and Alagoas viruses

Abstract: In Brazil and Argentina, vesicular stomatitis (VS) is caused by distinct viral strains serologically related to the classical vesicular stomatitis virus Indiana (VSIV), namely VS Indiana-2 (VSIV-2) and VS Indiana-3 (VSIV-3). Here we describe the full-length genomic sequences and organization of the prototype strains of VSIV-2 Cocal virus (COCV) and VSIV-3 Alagoas virus (VSAV). These viruses showed similar genomic organizations to VSIV field isolates except that the non-structural C'/C proteins, markedly conser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Position -3 from the start codon of the P gene is a C, consistent with Kozak’s rules for leaky scanning through an upstream AUG codon (Kozak, 1989). The predicted DURV C protein is 136 aa in length, which was 85 aa shorter than the TUPV homolog (221 aa), but significantly larger than the C′ proteins reported for VSINV (67 aa) and VSVNJV (65 aa) or the putative C proteins reported for additional rhabdoviruses (Spiropoulou and Nichol, 1993; Schütze et al ., 1999; Marriott, 2005; Pauszek et al ., 2008; Tao et al ., 2008). BLASTp analysis of the C protein of DURV revealed that it shared homologies, covering very similar regions of the DURV C protein (encompassing aa positions 15–75) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Position -3 from the start codon of the P gene is a C, consistent with Kozak’s rules for leaky scanning through an upstream AUG codon (Kozak, 1989). The predicted DURV C protein is 136 aa in length, which was 85 aa shorter than the TUPV homolog (221 aa), but significantly larger than the C′ proteins reported for VSINV (67 aa) and VSVNJV (65 aa) or the putative C proteins reported for additional rhabdoviruses (Spiropoulou and Nichol, 1993; Schütze et al ., 1999; Marriott, 2005; Pauszek et al ., 2008; Tao et al ., 2008). BLASTp analysis of the C protein of DURV revealed that it shared homologies, covering very similar regions of the DURV C protein (encompassing aa positions 15–75) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Like TUPV and most members of the genus Vesiculovirus , the DURV genome encodes a putative C protein from a second overlapping reading frame in the P gene (Spiropoulou and Nichol, 1993; Kretzschmar et al ., 1996; Springfeld et al ., 2005; Pauszek et al ., 2008). The DURV C protein was not conserved among related viruses, as it exhibited an 8 and 14% amino acid identity to the C proteins of TUPV and VSINV, respectively (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…This relatively simple genome organization is similar to that of vesiculoviruses. 30 Based on the N and L phylogenies and full genome nt sequence pairwise comparisons, the ledanteviruses can be further subdivided into three subgroups. This is partially supported by the complement fixation tests reported previously, although strong serological cross-reactions were generally only observed between closely related viruses (BARV and FUKV; KEUV, and LEDV); NISV and FKRV were not included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…13 The product of the current research is a field-evaluated, rapid, robust, realtime RT-PCR that identifies all VS virus isolates in Central and North America in as little as 4 hr using dry reagents and portable instrumentation. The assay is selfcorrecting in that the isolation of VS virus from a PCRnegative case signals a previously unrecognized virus that can be sequenced to provide a rapid modification of the assay.…”
Section: Discussionmentioning
confidence: 99%